Comparative Study of Robot Framework and Cucumber as BDD Automated Testing Tools - Khaerunnisa Khaerunnisa; Nungki Selviandro; Rosa Reska Riskiana (ULTIMATICS, 2023)
Automation testing is much more efficient and accurate, the script is easy to document, and update compared to manual testing. Testing a website may necessitate time and effort to learn the tools to be used. Cucumber and Robot Framework are well-known open-source frameworks, according to Stack Overflow and GitHub. Cucumber and Robot Framework are known on an international scale, especially Robot Framework, which is often used by large companies. Each uses the Java and Python languages, which both support BDD. The comparative efforts of the two tools aim to help testers compare and determine automated testing tools in the BisOps Logee Port Web Admin case study based on the effectiveness and efficiency of the tools and create specific test cases as test documentation so that testers do not need to spend time analyzing both. Because this research involves evaluation and comparison, several criteria were chosen to support the evaluation process, namely functionality, reliability, usability, performance efficiency, and portability. The results of this study show that both tools can be recommended for novice QA's who want to learn the basics of automation by implementing BDD. Meanwhile, for QA's who have done automation before and want to do more in-depth configuration and reporting, it is recommended to use Robot Framework because the syntax is short, has lots of keywords that make it easier for testers, and can make the testing system shorter but more specific.